Ambition in America : political power and the collapse of citizenship - Becker, Jeffrey A., 1968- (University Press of Kentucky, 2014)
Most Americans admire the determination and drive of artists, athletes, and CEOs, but they seem to despise similar ambition in their elected officials. The structure of political representation and the separation of powers detailed in the United States Constitution were intended to restrain self-interested ambition. Because not all citizens have a desire to rule, republican democracies must choose leaders from pools of ambitious candidates while trying to prevent those same people from exploiting public power to dominate the less ambitious. Ambition in America: Political Power and the Collapse.